Findings in an Elderly Patient after a Fall - Qasem M. Aljabr, (Journal of King Abdulaziz University: Medical Sciences, 2023)
A 76-year-old male presented with neck pain beginning a month earlier, when he tripped over a ledge while exiting his truck. The patient landed on his face and lost consciousness. In the emergency room, the initial work up, including a head computed tomography scan, came back negative, but the fall work-up was incomplete. He was discharged with a physical therapy appointment to manage his neck pain but did not go. The patient’s pain continued for another four weeks before he went to the clinic. The pain was located at the midline of his posterior cervical spine with limited range of motion. He was otherwise asymptomatic. A more comprehensive fall assessment and work-up was completed. An immediate neck computed tomography scan was ordered and revealed subacute Stage 2 odontoid fractures. The patient was placed in a neck collar. An urgent appointment with the neurosurgery clinic was requested. The neurosurgeon reviewed the neck computed tomography scan; a follow up by magnetic resonance imaging confirmed the findings. After discussing treatment options, the patient agreed to proceed with fusion surgery. This case demonstrates the importance of performing a complete fall assessment and workup to ensure early detection and prevention of serious or life-threatening injuries.